High-thermal-conductivity and high-resilience silica gel material and preparation method thereof
By introducing graphite and composite thermal fibers into the thermally conductive silicone material, a dense thermal conductivity network is formed, which solves the contradiction between thermal conductivity and mechanical properties, and achieves high thermal conductivity and high rebound silicone materials to meet the heat dissipation needs of complex electronic and electrical integration modules.
Patent Information
- Application Number
- CN202510729445.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-03
- Publication Date
- 2025-07-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While the existing thermally conductive silicone materials improve thermal conductivity, their mechanical properties have decreased, which cannot meet the heat dissipation needs of complex electronic and electrical integrated modules.
Graphite and composite thermal fibers are used as thermal fillers. The composite thermal fibers are made of PBA-PEG derivatives and transition metal sulfides. A dense thermal network is formed through electrostatic conjugated spinning technology to enhance the heat transfer path.
The thermal conductivity of silicone materials is improved, while maintaining or improving the mechanical properties, forming an efficient three-dimensional thermal conductivity network, and enhancing the heat dissipation ability.
Smart Images

Figure CN120365753A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of thermal conductive silicone, and particularly relates to a high thermal conductivity and high resilience silicone material and a preparation method thereof. Background Art
[0002] With the rapid replacement of electronic products, electronic and electrical devices are gradually becoming miniaturized, high power density, highly integrated, and multi-layered. The assembly conditions between components are becoming more and more demanding, resulting in a rapid increase in the heat generated when electronic devices work, shortening the service life, and seriously affecting their performance. Therefore, materials with high thermal conductivity and high thermal stability are needed to meet the high heat dissipation performance requirements of "complicated" electronic integration modules.
[0003] Silicone (SG), as a commonly used electronic and electrical material, has advantages such as good electrical insulation, adhesion, and sealing, but its low thermal conductivity limits its application in more fields. In this regard, the silicone matrix is usually mixed with thermal conductive insulating fillers to make thermal conductive silicone to improve the thermal conductivity, and then it can be applied to the gap parts that need heat dissipation and heat transfer in the electronic field, thereby improving the overall heat dissipation ability of electronic devices.
[0004] In thermal conductive silicone, the selection of thermal conductive insulating fillers will directly affect the thermal conductivity and stability of thermal conductive silicone. For example, the patent application document with the publication number CN118909441A discloses a low-expansion thermal conductive silicone composition. The thermal conductive fillers used include a first powder and a flaky composite powder. The flaky composite powder includes a flaky substrate powder and a second powder loaded on the surface of the flaky substrate powder. The loaded powder is a negative thermal expansion material and / or a low thermal expansion material; the thermal expansion coefficient of the low thermal expansion material is less than that of the flaky substrate powder. Within the service temperature range of the thermal conductive silicone, the flaky composite powder with a predetermined orientation is beneficial to reducing the thermal expansion degree in the thickness direction of the thermal conductive silicone.
[0005] Another example is the patent application document with the publication number CN117924776A, which discloses a thermal conductive silicone gasket and a preparation method thereof. The thermal conductive material layer includes the following components in parts by weight: 15-30 parts of methyl vinyl silicone raw rubber; 3-10 parts of hydrogen-containing silicone oil; 1-3 parts of platinum catalyst; 40-50 parts of modified alumina; 20-35 parts of modified hexagonal boron nitride; 2-5 parts of vulcanizing agent; 0.5-2 parts of inhibitor; the thermal conductive material is alumina surface-modified with a silane coupling agent and hexagonal boron nitride modified with cetyltrimethylammonium bromide, thereby improving the thermal conductivity of the silicone material to a certain extent.
[0006] For the above-mentioned thermal conductive silicone materials, on the one hand, the introduction of a large amount of sheet-like composite powders or materials such as alumina and boron nitride will lead to a decrease in the mechanical properties of the silicone materials, such as elasticity and toughness. On the other hand, the thermal conductivity improvement of pure powders or sheet-like thermal conductive fillers is limited and cannot well meet the heat dissipation requirements of the current "complex" electronic and electrical integration modules. Therefore, it is necessary to develop thermal conductive silicone materials with higher thermal conductivity and mechanical properties. Summary of the Invention
[0007] In view of the above problems, in order to further improve the thermal conductivity and mechanical properties of the thermal conductive silicone materials, the present application provides a high thermal conductivity and high resilience silicone material and its preparation method.
[0008] The present application first provides a high thermal conductivity and high resilience silicone material, including a silicone matrix and a thermal conductive filler. The thermal conductive filler includes graphite and composite thermal conductive fibers; the composite thermal conductive fibers are prepared from PBA-PEG derivatives and transition metal sulfides.
[0009] Furthermore, it further includes one or more of the following features: A1) The mass ratio of graphite to composite thermal conductive fibers is 1:(0.6 - 1); A2) The graphite is flake graphite with a mesh number of 50 - 500; A3) The graphite is modified with a silane coupling agent; A4) The mass ratio of the silicone matrix to the thermal conductive filler is 1:(0.1 - 0.4); A5) The silicone matrix is a two-component organosilicon rubber.
[0010] Furthermore, the composite thermal conductive fibers are prepared by the following steps: 1) React NH2-PEG-NH2 and PBA under a catalyst to obtain PBA-PEG derivatives, and then dissolve the PBA-PEG derivatives in DMF to obtain precursor solution one; 2) Dissolve polyacrylamide and choline chloride in DMF, and then add transition metal sulfides and heat to mix well to obtain precursor solution two; 3) Take precursor solution one and precursor solution two for conjugate electrospinning to obtain the product.
[0011] Furthermore, it further includes one or more of the following features: 11) The average molecular weight of PEG in NH2-PEG-NH2 is 400 - 1200; 12) The content of PBA-PEG derivatives in precursor solution one is 10 - 15 wt%; 13) The catalyst is sodium borohydride.
[0012] Furthermore, it includes one or more of the following features: 21) In the second precursor solution, the mass ratio of polyacrylamide, choline chloride, and transition metal sulfide is 1:(0.5 - 0.75):(1 - 2); 22) The average particle size of the transition metal sulfide is 50 - 200 nm.
[0013] Furthermore, it further includes one or more of the following features: 31) In the conjugated precursor, the flow rate ratio of the first precursor solution to the second precursor solution is 1:(1.5 - 2.5); 32) The composite heat-conducting fiber obtained from the conjugated precursor is cryogenically pulverized, and the average length is 0.05 - 0.2 mm.
[0014] Furthermore, the transition metal sulfide is prepared by the following steps: S1: Dissolve silver nitrate and thioacetamide in deionized water, then conduct a hydrothermal reaction under sealed conditions, collect the product, and wash to obtain silver sulfide particles; S2: Take ammonium tetrathiomolybdate, UiO-66-NH2, silver sulfide particles, and deionized water, mix them evenly, conduct a hydrothermal reaction under sealed conditions, collect the product, wash, and freeze-dry to obtain it.
[0015] Furthermore, in the step S1, the temperature of the sealed hydrothermal reaction is 190 - 220 °C.
[0016] Furthermore, in the step S2, the mass ratio of ammonium tetrathiomolybdate to silver sulfide particles is 1:(0.2 - 0.5).
[0017] This application also provides a preparation method of a high heat-conducting and high-elasticity silica gel material, including the following steps: Mix the heat-conducting filler and the silica gel matrix evenly to obtain it.
[0018] Compared with the prior art, this application has the following beneficial effects: 1. Based on the traditional graphite filler, this application introduces composite heat-conducting fibers. On the one hand, it can reduce the addition amount of graphite filler and the influence on the mechanical properties of the silica gel matrix; on the other hand, the graphite filler and the composite heat-conducting fibers can form a more dense and effective three-dimensional heat-conducting network in the silica gel matrix. Graphite serves as a heat-conducting anchor point, and the composite heat-conducting fibers serve as a heat-transferring connecting chain. The two cooperate to increase the heat transfer path, thereby improving the heat conductivity of the silica gel.
[0019] 2. The composite thermal conductive fiber of the present application is prepared by using PBA-PEG derivative and transition metal sulfide as compound components. Among them, the PBA-PEG derivative can improve the compatibility between the thermal conductive composite fiber and the silica gel matrix, make the orientation of the fiber in the silica gel matrix more uniform, thereby enhancing the anisotropy of heat transfer, enabling heat to be quickly dissipated along the thermal conductive network. Moreover, the boron atoms in the PBA-PEG derivative and the transition metal sulfide can jointly reduce the interfacial thermal resistance and energy loss between the fiber and the matrix, thereby enhancing the cross-plane thermal conductivity of the thermal conductive network. Description of the Drawings
[0020] Figure 1 It is a schematic diagram of the thermal conductivity performance data of the silica gel materials in Examples 1-2 and Control Groups 1-2 of the present application.
[0021] Figure 2 It is a schematic diagram of the mechanical property data of the silica gel materials in Examples 1-2 and Control Groups 1-2 of the present application. Detailed Embodiments
[0022] Next, the technical solutions in the embodiments of the present application will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative efforts shall fall within the protection scope of the present application.
[0023] Through a large number of experimental studies, the present application screened traditional thermal conductive fillers such as graphite, boron nitride, alumina, zinc oxide, silicon nitride, silica, etc., and tested fiber thermal conductive materials such as carbon fiber, cellulose fiber, etc., and finally selected the research and development direction of compounding flaky graphite filler and fiber filler. Specifically, the present application develops and provides a high thermal conductivity and high resilience silica gel material, including a silica gel matrix and a thermal conductive filler, and the thermal conductive filler includes graphite and a composite thermal conductive fiber; the composite thermal conductive fiber is prepared from PBA-PEG derivative and transition metal sulfide.
[0024] Furthermore, it further includes one or more of the following features: A1) The mass ratio of graphite to the composite thermal conductive fiber is 1:(0.6 - 1); A2) The graphite is flake graphite with a mesh number of 50 - 500; A3) The graphite is modified by a silane coupling agent; A4) The mass ratio of the silica gel matrix to the thermal conductive filler is 1:(0.1 - 0.4); A5) The silica gel matrix is a two-component organic silica gel.
[0025] In some specific embodiments, the mass ratio of graphite to the composite heat-conducting fiber can be 1:0.6, 1:0.65, 1:0.7, 1:0.75, 1:0.8, 1:0.85, 1:0.9, 1:0.95, 1:1. Usually, when the mass ratio of graphite to the composite heat-conducting fiber is 1:0.75, better experimental results can be obtained.
[0026] In some specific embodiments, the graphite is flake graphite, and the mesh number can be 50, 100, 200, 325, 500. More preferably, usually, when the mesh number is 50, better effects can be obtained.
[0027] In some specific embodiments, the graphite is modified with a silane coupling agent, and the silane coupling agent is one of KH-550, KH-580, and A-171. More preferably, when the silane coupling agent is KH-550, the effect is better.
[0028] In some specific embodiments, the mass ratio of the silica gel matrix to the heat-conducting filler can be 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4. More preferably, usually, when the mass ratio of the silica gel matrix to the heat-conducting filler is 1:0.3, the experimental results are better.
[0029] Furthermore, the composite heat-conducting fiber is prepared by the following steps: 1) React NH2-PEG-NH2 and PBA under a catalyst to obtain a PBA-PEG derivative, and then dissolve the PBA-PEG derivative in DMF to obtain a first precursor solution; 2) Dissolve polyacrylamide and choline chloride in DMF, and then add a transition metal sulfide and heat to mix well to obtain a second precursor solution; 3) Take the first precursor solution and the second precursor solution for conjugate spinning to obtain the product.
[0030] Furthermore, it further includes one or more of the following features: 11) The average molecular weight of PEG in NH2-PEG-NH2 is 400-1200; 12) The content of the PBA-PEG derivative in the first precursor solution is 10-15 wt%; 13) The catalyst is sodium borohydride.
[0031] In some specific embodiments, the average molecular weight of PEG in NH2-PEG-NH2 can be 400, 600, 800, 1000, 1200. Usually, when the average molecular weight of PEG in NH2-PEG-NH2 is 800, the effect is better.
[0032] In some specific embodiments, the content of the PBA-PEG derivative in the first precursor solution can be 10.5 wt%, 11 wt%, 11.5 wt%, 12 wt%, 12.5 wt%, 13 wt%, 13.5 wt%, 14 wt%, 14.5 wt%, 15 wt%. Usually, when the content of the PBA-PEG derivative in the first precursor solution is 12.5 wt%, better experimental results can be obtained.
[0033] Furthermore, it includes one or more of the following features: 21) In the second precursor solution, the mass ratio of polyacrylamide, choline chloride, and transition metal sulfide is 1:(0.5 - 0.75):(1 - 2); 22) The average particle size of the transition metal sulfide is 50 - 200 nm.
[0034] Furthermore, it also includes one or more of the following features: 31) In the conjugate precursor, the flow rate ratio of the first precursor solution to the second precursor solution is 1:(1.5 - 2.5); 32) The composite heat-conducting fiber obtained from the conjugate precursor is cryogenically pulverized, and its average length is 0.05 - 0.2 mm.
[0035] Furthermore, the transition metal sulfide is prepared by the following method: S1: Dissolve silver nitrate and thioacetamide in deionized water, then conduct a hydrothermal reaction under sealed conditions, collect the product, and wash to obtain silver sulfide particles; S2: Take ammonium tetrathiomolybdate, UiO-66-NH2, silver sulfide particles, and deionized water, mix them evenly, conduct a hydrothermal reaction under sealed conditions, collect the product, wash, and freeze-dry to obtain it.
[0036] Furthermore, in step S1, the temperature of the sealed hydrothermal reaction is 190 - 220 °C.
[0037] Furthermore, in step S2, the mass ratio of ammonium tetrathiomolybdate to silver sulfide particles is 1:(0.2 - 0.5).
[0038] In some specific embodiments, in the second precursor solution, the mass ratio of polyacrylamide, choline chloride, and transition metal sulfide can be 1:0.5:1, 1:0.55:1, 1:0.6:1, 1:0.65:1, 1:0.7:1, 1:0.75:1, 1:0.5:1.1, 1:0.55:1.2, 1:0.6:1.5, 1:0.65:1.7, 1:0.7:1.8, 1:0.75:2. Usually, when the mass ratio of polyacrylamide, choline chloride, and transition metal sulfide in the second precursor solution is 1:0.5:2, better experimental results can be obtained.
[0039] In some specific embodiments, the average particle size of the transition metal sulfide can be 50 nm, 70 nm, 80 nm, 100 nm, 120 nm, 150 nm, 200 nm. Usually, if the average particle size of the transition metal sulfide is too large, it is easy to cause plugging, and if the average particle size of the transition metal sulfide is too large, it is easy to cause agglomeration. More preferably, when the average particle size of the transition metal sulfide is 100 nm, better effects can be achieved.
[0040] In some specific embodiments, in the conjugated precursor, the flow rate ratio of precursor liquid one to precursor liquid two can be 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5. Usually, when the flow rate ratio of precursor liquid one to precursor liquid two is 1:2.0, better experimental effects can be obtained.
[0041] In some specific embodiments, in step S2, the mass ratio of ammonium tetrathiomolybdate to silver sulfide particles can be 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5. More preferably, usually, in step S2, when the mass ratio of ammonium tetrathiomolybdate to silver sulfide particles is 1:0.25, better experimental effects can be obtained.
[0042] Example 1 The high thermal conductivity and high resilience silicone material of this example is composed of a silicone matrix and a thermal conductive filler in a mass ratio of 1:0.3. The thermal conductive filler is composed of graphite and composite thermal conductive fibers in a mass ratio of 1:0.75. The graphite is flake graphite, which is modified by KH-550 and has a mesh number of 50.
[0043] The composite thermal conductive fibers of this example are prepared by the following steps: 1) Add 0.2 mol of NH2-PEG-NH2 (the average molecular weight of PEG is 800), 0.5 mol of PBA (2-aldehyde phenylboronic acid), and 200 mL of DMSO to a 1500 mL four-necked flask, mix evenly, and react under the catalysis of sodium borohydride to obtain a PBA-PEG derivative. Then dissolve the PBA-PEG derivative in DMF to obtain precursor liquid one, and control the content of the PBA-PEG derivative in precursor liquid one to be 12.5 wt%; 2) Add 20 g of polyacrylamide and 10 g of choline chloride to 500 mL of DMF in a beaker, and then add 40 g of transition metal sulfide (zinc sulfide, average particle size 100 nm), heat to 65 °C, and mix well to obtain precursor liquid two; 3) Precursor solution 1 and precursor solution 2 are taken and electrostatically conjugated through the positive electrode syringe and the negative electrode syringe respectively, and the composite thermal conductive fiber is collected on the receiving roller; Among them, precursor liquid 1 is sprayed from the positive electrode syringe, and the working voltage of the positive electrode syringe is 15kV. Precursor liquid 2 is sprayed from the negative electrode syringe, and the working voltage of the negative electrode syringe is 17kV. The flow rate ratio of precursor liquid 1 to precursor liquid 2 is 1:2.0, and the total flow rate of precursor liquid 1 and precursor liquid 2 is 4mL / min, and the winding speed is 0.25mm / s.
[0044] The preparation method of the high thermal conductivity and high resilience silicone material of this embodiment includes the following steps: mixing component A and component B of organic silicone (model 196, manufacturer: Shenzhen Aosbon Co., Ltd.) evenly, then adding thermal conductive filler and continuing to stir and mix, then transferring to a vacuum drying oven for degassing, and finally putting into an oven and curing at 100°C for 30 minutes.
[0045] Example 2 The high thermal conductivity and high resilience silicone material of this embodiment is composed of a silicone matrix and a thermal conductive filler in a mass ratio of 1:0.3. The thermal conductive filler is composed of graphite and composite thermal conductive fiber in a mass ratio of 1:0.75. The graphite is flake graphite modified by KH-550 and has a mesh size of 50.
[0046] The composite thermally conductive fiber of this embodiment is prepared by the following steps: 1) Add 0.2 mol NH2-PEG-NH2 (the average molecular weight of PEG is 800), 0.5 mol PBA (2-formylphenylboronic acid) and 200 mL DMSO into a 1500 mL four-necked flask and mix well. React under the catalysis of sodium borohydride to obtain PBA-PEG derivatives. Then, the PBA-PEG derivatives are dissolved in DMF to obtain a precursor solution 1. The content of the PBA-PEG derivatives in the precursor solution 1 is controlled to be 12.5 wt%; 2) Add 20g polyacrylamide and 10g choline chloride into a beaker and dissolve them in 500mL DMF, then add 40g transition metal sulfide (average particle size 100nm), heat to 65°C and mix thoroughly to prepare precursor solution 2; 3) Precursor solution 1 and precursor solution 2 are taken and electrostatically conjugated through the positive electrode syringe and the negative electrode syringe respectively, and the composite thermal conductive fiber is collected on the receiving roller; Among them, precursor liquid 1 is sprayed from the positive electrode syringe, and the working voltage of the positive electrode syringe is 15kV. Precursor liquid 2 is sprayed from the negative electrode syringe, and the working voltage of the negative electrode syringe is 17kV. The flow rate ratio of precursor liquid 1 to precursor liquid 2 is 1:2.0, and the total flow rate of precursor liquid 1 and precursor liquid 2 is 4mL / min, and the winding speed is 0.25mm / s.
[0047] The transition metal sulfide of this embodiment is prepared by the following steps: S1: 1.67 g of silver nitrate and 0.75 g of thioacetamide were dissolved in 500 mL of deionized water, and then transferred to a PTFE-lined autoclave for hydrothermal reaction at 200 °C for 20 h under sealed conditions. The product was collected, washed with anhydrous ethanol and distilled water, and freeze-dried to obtain silver sulfide particles; S2: Take 1g of ammonium tetrathiomolybdate, 0.05g of UiO-66-NH2 (zirconium aminophthalate MOF), 0.25g of silver sulfide particles, and 500mL of deionized water, mix them evenly, and then transfer them to a PTFE-lined high-pressure reactor. Perform hydrothermal reaction at 200°C under sealed conditions for 20h. Collect the products, wash them with anhydrous ethanol and distilled water, freeze-dry them, and grind them.
[0048] The preparation method of the high thermal conductivity and high resilience silicone material of this embodiment includes the following steps: mixing component A and component B of organic silicone (model 196, manufacturer: Shenzhen Aosbon Co., Ltd.) evenly, then adding thermal conductive filler and continuing to stir and mix, then transferring to a vacuum drying oven for degassing, and finally putting into an oven and curing at 100°C for 30 minutes.
[0049] Control group 1 The silica gel material of the control group is composed of a silica gel matrix and a thermal conductive filler in a mass ratio of 1:0.3. The thermal conductive filler is composed of graphite and composite thermal conductive fiber in a mass ratio of 1:0.75. The graphite is flake graphite modified by KH-550 and has a mesh size of 50.
[0050] The composite thermal conductive fiber of the control group was prepared by the following steps: 1) Add 0.2 mol NH2-PEG-NH2 (the average molecular weight of PEG is 800), 0.5 mol PBA (2-formylphenylboronic acid) and 200 mL DMSO into a 1500 mL four-necked flask and mix well. React under the catalysis of sodium borohydride to obtain PBA-PEG derivatives. Then, the PBA-PEG derivatives are dissolved in DMF to obtain a precursor solution 1. The content of the PBA-PEG derivatives in the precursor solution 1 is controlled to be 12.5 wt%; 2) Add 20g polyacrylamide and 10g choline chloride into a beaker and dissolve them in 500mL DMF, then add 40g nano-alumina (average particle size 100nm) and heat to 65°C and mix thoroughly to prepare precursor solution 2; 3) Precursor solution 1 and precursor solution 2 are taken and electrostatically conjugated through the positive electrode syringe and the negative electrode syringe respectively, and the composite thermal conductive fiber is collected on the receiving roller; Among them, the first precursor liquid is ejected from the positive electrode syringe, the working voltage of the positive electrode syringe is 15 kV, the second precursor liquid is ejected from the negative electrode syringe, the working voltage of the negative electrode syringe is 17 kV, the flow rate ratio of the first precursor liquid to the second precursor liquid is 1:2.0, the total flow rate of the first precursor liquid and the second precursor liquid is 4 mL / min, and the winding speed is 0.25 mm / s.
[0051] The preparation method of the silicone material in this control group includes the following steps: Mix the A component and B component of the organosilicone (model 196, manufacturer: Shenzhen Ausbond Co., Ltd.) evenly, then add the heat-conducting filler and continue to stir and mix, then transfer it to a vacuum drying oven for defoaming, and finally put it into an oven and cure it at 100 °C for 30 min to obtain.
[0052] Control Group 2 The silicone material in this control group is composed of a silicone matrix and a heat-conducting filler in a mass ratio of 1:0.3. The heat-conducting filler is composed of graphite and composite heat-conducting fibers in a mass ratio of 1:0.75. The graphite is flake graphite, which is modified by KH-550 and has a mesh number of 50.
[0053] The composite heat-conducting fibers in this control group are prepared by the following steps: 1) Add 20 g of polyacrylamide and 10 g of choline chloride to 500 mL of DMF in a beaker, then add 40 g of transition metal sulfide (average particle size 100 nm) and heat to 65 °C for full mixing to obtain a precursor liquid; 3) Take the precursor liquid for electrostatic conjugation precursor, and collect the composite heat-conducting fibers on the receiving roller; Among them, the precursor liquid is ejected from the positive electrode syringe, the working voltage of the positive electrode syringe is 15 kV, the receiving roller is the negative electrode, the working voltage is 17 kV, the total flow rate of the precursor liquid is 4 mL / min, and the winding speed is 0.25 mm / s.
[0054] The transition metal sulfide in this control group is prepared by the method of the following steps: S1: Dissolve 1.67 g of silver nitrate and 0.75 g of thioacetamide in 500 mL of deionized water, then transfer it to a high-pressure reaction kettle with a PTFE inner lining, and carry out a hydrothermal reaction at 200 °C for 20 h under sealed conditions. Collect the product, wash it with absolute ethanol and distilled water, and freeze-dry to obtain silver sulfide particles; S2: Take 1 g of ammonium tetrathiomolybdate, 0.05 g of UiO-66-NH2 (zirconium aminoterephthalate MOF), 0.25 g of silver sulfide particles, and 500 mL of deionized water and mix them evenly. Then transfer it to a high-pressure reaction kettle with a PTFE inner lining, and carry out a hydrothermal reaction at 200 °C for 20 h under sealed conditions. Collect the product, wash it with absolute ethanol and distilled water, and freeze-dry and grind to obtain.
[0055] The preparation method of the silicone material in this control group includes the following steps: Mix the A and B components of the organosilicon rubber (model 196, manufacturer: Shenzhen Ausbond Co., Ltd.) evenly, then add the thermal conductive filler and continue to stir and mix. Then transfer it to a vacuum drying oven for degassing, and finally put it into an oven and cure it at 100 °C for 30 min to obtain the product.
[0056] Performance testing 1. Take the silicone materials of Examples 1-2 and Control Groups 1-2, and use the ASTM-D5470 test standard to test the thermal conductivity of the silicone materials. The sample size is cut to 25 mm × 25 mm × 4 mm. Place the heat source (electric heater) and the cooling source (constant temperature water bath) on both sides of the sample respectively, and place them in close contact with both ends of the sample to form a stable thermal gradient. Arrange thermocouples at different positions of the sample to measure the temperature distribution. The test results are as Figure 1 shown. It can be seen that the silicone material of this application has a higher thermal conductivity, and the heat transfer along the direction perpendicular to the sample thickness is relatively efficient.
[0057] 2. Take the silicone materials of Examples 1-2 and Control Groups 1-2, and use a universal electronic tensile testing machine to test the mechanical properties. The specimen size is 10 mm × 4 mm × 1 mm, the experimental temperature is room temperature, and the tensile rate is 200 mm / min. Each sample is tested 3 times and the average value is taken. The test results are as Figure 2 shown. It can be seen that the introduction of the thermal conductive filler does not cause a significant decrease in the mechanical properties of the silicone material, and the excellent mechanical properties of the silicone matrix material are still maintained.
[0058] Although the present application has been described in detail with reference to the foregoing embodiments, for those skilled in the art, they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements for some of the technical features. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present invention.
Claims
1. A high thermal conductivity and high resilience silicone material, characterized in that: It includes a silica gel matrix and heat-conducting fillers. The heat-conducting fillers include graphite and composite heat-conducting fibers; the composite heat-conducting fibers are prepared from PBA-PEG derivatives and transition metal sulfides.
2. The highly thermally conductive and highly resilient silicone material according to claim 1, wherein: It also includes one or more of the following features: A1) The mass ratio of graphite to composite heat-conducting fibers is 1:(0.6 - 1); A2) The graphite is flake graphite with a mesh number of 50 - 500; A3) The graphite is modified by a silane coupling agent; A4) The mass ratio of the silica gel matrix to the heat-conducting fillers is 1:(0.1 - 0.4); A5) The silica gel matrix is a two-component organic silica gel.
3. The highly thermally conductive and highly resilient silicone material according to claim 1, characterized in that: The composite heat-conducting fibers are prepared by the following steps: 1) React NH2-PEG-NH2 and PBA under a catalyst to obtain PBA-PEG derivatives, and then dissolve the PBA-PEG derivatives in DMF to obtain the first precursor solution; 2) Dissolve polyacrylamide and choline chloride in DMF, and then add transition metal sulfides and heat to mix thoroughly to obtain the second precursor solution; 3) Take the first precursor solution and the second precursor solution for conjugate spinning to obtain the product.
4. The highly thermally conductive and highly resilient silicone material according to claim 3, wherein: It also includes one or more of the following features: 11) The average molecular weight of PEG in NH2-PEG-NH2 is 400 - 1200; 12) The content of PBA-PEG derivatives in the first precursor solution is 10 - 15 wt%; 13) The catalyst is sodium borohydride.
5. The high thermal conductivity and high resilience silicone material according to claim 3, characterized in that: The above includes one or more of the following features: 21) In the second precursor solution, the mass ratio of polyacrylamide, choline chloride, and transition metal sulfides is 1:(0.5 - 0.75):(1 - 2); 22) The average particle size of the transition metal sulfides is 50 - 200 nm.
6. The highly thermally conductive and highly resilient silicone material according to claim 3, wherein: It also includes one or more of the following features: 31) In the conjugate precursor, the flow rate ratio of the first precursor solution to the second precursor solution is 1:(1.5 - 2.5); 32) The composite heat-conducting fibers obtained from the conjugate precursor are cryogenically pulverized, and the average length is 0.05 - 0.2 mm.
7. The highly thermally conductive and highly resilient silicone material according to any one of claims 1-6, characterized in that: The transition metal sulfides are prepared by the following method: S1: Dissolve silver nitrate and thioacetamide in deionized water, and then carry out a hydrothermal reaction under sealed conditions, collect the product, and wash to obtain silver sulfide particles; S2: Take ammonium tetrathiomolybdate, UiO-66-NH2, silver sulfide particles, and deionized water, mix them evenly, carry out a hydrothermal reaction under sealed conditions, collect the product, wash, and freeze-dry to obtain the product.
8. The highly thermally conductive and highly resilient silicone material according to claim 7, wherein: In the step S1, the temperature of the sealed hydrothermal reaction is 190 - 220 °C.
9. The highly thermally conductive and highly elastic silicone material according to claim 7, wherein: In the step S2, the mass ratio of ammonium tetrathiomolybdate to silver sulfide particles is 1:(0.2 - 0.5).
10. A preparation method of a high thermal conductivity and high resilience silicone material, characterized in that: It includes the following steps: Mix the heat-conducting fillers and the silica gel matrix evenly to obtain the product.
Citation Information
Patent Citations
Heat-conducting silica gel gasket and preparation method thereof
CN117924776A
Low-expansion heat-conducting silica gel composition, heat-conducting silica gel sheet and preparation method of silica gel sheet
CN118909441A